A photo-stable and reversible pH-responsive nano-agent based on the NIR phenazine dye for photoacoustic imaging-guided photothermal therapy. Issue 73 (23rd August 2019) - Yan, Yongchao; Fu, Hao; Wang, Jian; Chen, Chuanrong; Wang, Qi; Duan, Yourong; Hua, Jianli
Abstract : A photo-stable and reversible pH-responsive phenazine dye displayed an obvious NIR absorption in a weak acid environment of tumor. The dye assembled into nanoparticles was developed for photoacoustic imaging-guided photothermal therapy in mice. Abstract : Different from traditional "always on" photothermal therapy (PTT) agents, tumor microenvironment responsive agents showed more tumor specificity and lower photo-toxicity to normal tissues. Herein, a photo-stable and reversible pH responsive phenazine dye (PIOH ) was synthesized and assembled with liposomes forming nanoparticles (PIOH-NPs ), which exhibited a strong NIR absorption in a weak acid environment and were successfully utilized for photoacoustic (PA) imaging-guided photothermal therapy in mice.